2020
DOI: 10.26858/ja.v7i2.15343
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Problem Based Learning (PBL) Towards Learning Outcomes Through Critical Thinking Skills

Abstract: The purpose of this study is to determie the effect of Problem Based Learning (PBL) on learning outcomes through critical thinking. This research is quasi experimental with posttest only control group design. Analysis of data using Two Way Anova. The result of this research shows that (1) There is a difference between students who are taught by using teaching model PBL and students who are not taught by using teaching model PBL. (2) There is a difference in learning outcomes between high critical thinking skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Student discussion activity is one aspect of critical thinking skills. These results are relevant to the conclusions of the study which show that PBL is able to have a good impact on improving critical thinking skills through the process of problem analysis and knowledge sharing between students (Benedicto & Andrade, 2022;Dharma et al, 2020;Dwi Anggriani & Eko Atmojo, 2022;Fadilla et al, 2021;Pramestika et al, 2020). In addition, the group discussion process is also able to support the improvement of students' critical thinking skills (Maryani et al, 2018).…”
Section: Table 3 T -Testmentioning
confidence: 59%
See 1 more Smart Citation
“…Student discussion activity is one aspect of critical thinking skills. These results are relevant to the conclusions of the study which show that PBL is able to have a good impact on improving critical thinking skills through the process of problem analysis and knowledge sharing between students (Benedicto & Andrade, 2022;Dharma et al, 2020;Dwi Anggriani & Eko Atmojo, 2022;Fadilla et al, 2021;Pramestika et al, 2020). In addition, the group discussion process is also able to support the improvement of students' critical thinking skills (Maryani et al, 2018).…”
Section: Table 3 T -Testmentioning
confidence: 59%
“…The application of the learning model implemented in class so far is considered capable of increasing students' critical thinking skills. Problem-Based Learning (PBL) is a learning model that is oriented toward the use of problems with real-world contexts that can train critical thinking skills and problem-solving as well as a comprehensive understanding of a material concept PBL can hone critical thinking skills because this model contains activity steps that require students to carry out discussions, exploration, inquiry, discovery, and problem-solving (Agustina et al, 2017;Ali, 2019;Benedicto & Andrade, 2022;Benediktus Tanujaya et al, 2017;Cheng & Liu, 2015;Dharma et al, 2020;Dwi Anggriani & Eko Atmojo, 2022;Fadilla et al, 2021;Hikmawati & Suryaningsih, 2020;Pramestika et al, 2020;Serezli et al, 2023;Widyatiningtyas et al, 2015). In other words, learning steps with this PBL model have the potential to improve students' mathematical critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…The same thing occurs in the science literacy skills of students with higher critical thinking skills (Rahayuni, 2016). The ability to think critically also has a positive impact on student learning outcomes, which is an indicator of the success of the academic process (Mulyanto et al, 2018;Miharja et al, 2019;Subiyantari et al, 2019;Dharma et al, 2020;Andayani et al, 2020). However, another study found that critical thinking skills did not affect student learning outcomes (Tabun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It aimed to imbue in students problem-solving skills for operationalisation in the 'real world', namely the clinical environment (Schmidt 2012). Problem-based learning is defined as a studentcentred pedagogical approach triggered by an authentic, ill-structured problem that requires the collaborative, active engagement of the students, who are understood as self-directed, active knowledge seekers and creators of knowledge when arriving at an academic resolution (Dharma, Tasrikah & Churiyah 2020). The teaching and learning process involved in PBL requires students to learn to be internally motivated, and self-driven in their pursuit of education and collaborate with others to become 'life-long learners' (Yew & Goh 2016).…”
Section: Introductionmentioning
confidence: 99%